2012
DOI: 10.1177/1523422312455626
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Work/Life Conflict and Life Satisfaction in Executives

Abstract: The Problem.Determining "what" and "how" people are satisfied personally and with work has become an ongoing stream of research for both academics and practitioners. Yet research has contributed to confusing the issue and has not been able to provide any distinct answers to this problem. The Solution.This study goes beyond current research by examining how problem-focused coping resources are used to ameliorate the negative relationship between work/life conflict and life satisfaction. Based on a sample of 491… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…For example, satisfied people have healthier mental states, lead more positive lives, and tend to have more satisfying relationships with their spouses (Diener & Seligman, ). Family‐related research has indicated that satisfied individuals tend to have stronger and more supportive families and friendships, which results in greater psychological benefits (McMillan & Morris, ). Therefore, employees who experience emotional exhaustion are more likely to experience a lower level of marital satisfaction.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…For example, satisfied people have healthier mental states, lead more positive lives, and tend to have more satisfying relationships with their spouses (Diener & Seligman, ). Family‐related research has indicated that satisfied individuals tend to have stronger and more supportive families and friendships, which results in greater psychological benefits (McMillan & Morris, ). Therefore, employees who experience emotional exhaustion are more likely to experience a lower level of marital satisfaction.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Based on Kahn, Wolfe, Quinn, Snoek, and Rosenthal's () inter‐role conflict theory, Greenhaus and Beutell () defined the WFC as “a form of inter‐role conflict in which the role pressures from the work and family domains are mutually incompatible in some respect” (p. 401). Since then, scholars (e.g., Greenhaus et al, ; Greenhaus & Beutell, ; Gutek, Searle, & Klepa, ; McMillan & Morris, ) have argued that WFC may go in either of two directions: WFC or FWC. Netemeyer et al () developed a measurement tool that takes into account two forms of WFC (e.g., the time‐based conflict and the strain‐based conflict), as well as these two directions (e.g., WFC and FWC).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Timor Leste is a new country in Asian has greatest challenges in relating to the human resources in developing a process of the country. The human resources (Mcmillan & Morris, 2012) become mind challenges for the country because after the early days of independent there very few numbers of Timorese have good education qualified to build the country. The Good human resources are achieved by the good education system (Alwell, Cobb, & Alwell, 2009).…”
Section: Introductionsmentioning
confidence: 99%